Health Problems and Health-seeking Behavior of Aged Population from Rural Area of South India: A Cross-sectional Study - Pravin N. Yerpude; Keerti S. Jogdand; Mohini S. Jogdand (Medical Research and Its Applications Vol. 9, 2024)
Introduction: Health status plays a very important role in the quality of life of an individual. With an increase in age, many health problems arise. Ageing of a population is a matter of great concern for the health sector. The elderly are, on the whole, less healthy than the non-elderly. Many health problems are known to increase with age and this demographic trend may lead to an increase in the absolute number of health conditions in the population. In addition, because there is a growing body of evidence that older people are at risk for multiple, co-morbid conditions, health care seeking will probably also increase. Aim: The present study aimed to assess the pattern of health problems and health-seeking behaviour of the elderly in rural areas of South India. Materials and Methods: The present descriptive cross-sectional study was conducted among the rural elderly population aged 60 years and above residing in the rural area of Prathipadu which is the field practice area of Dept of Community Medicine. The study was done from Oct 2011 to Dec 2011. Results: Most of the study subjects (65.5%) were in the age group of 60-69 years. 28.5% of the study subjects were illiterate. The majority (79.5%) were not working. Around 68.5% study subjects were having one or other health problems. 39.42% were suffering from locomotive disorders, followed by respiratory disorders (30.66%), hypertension (27.7%) and visual impairment (25.55%). Around 75.91% of study subjects were taking some kind of treatment. Around 41.35% of study subjects were complying with their treatment regime. The most common reason for non-compliance was the high cost of treatment (39.34%). Regarding the morbidity pattern of the older persons in the current study, locomotive disorders were found to be most common, followed by respiratory disorders and hypertension. Musculo-skeletal changes are one of the most important functional effects of ageing. There is a loss of bone mass with ageing. Conclusion: The findings of the study demonstrated that the majority of elderly people had one or more health issues, with motor abnormalities being the most prevalent. Additionally, while the majority of the participants were receiving treatment, there was a low level of adherence. The need for geriatric counseling facilities to address the medical, physiological, psychological, and social needs of the elderly is increasing.